1994
DOI: 10.1161/01.str.25.6.1265
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of transesophageal echocardiography and transcranial Doppler sonography with contrast medium for detection of patent foramen ovale.

Abstract: Background Patent foramen ovale as a possible stroke risk factor can be diagnosed with transcranial Doppler sonography (TCD) by detecting intravenous contrast medium crossing from the right to the left atrium. The present study evaluates the reliability of this method.Summary of Report We performed TCD and transesophageal echocardiography simultaneously in 50 patients using galactose microbubbles. We observed bubble signals passing the middle cerebral artery in 7 patients less than 20 seconds after injection; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
102
0
8

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(112 citation statements)
references
References 15 publications
2
102
0
8
Order By: Relevance
“…With contrast TT echocardiography, 4 TE echocardiography, 32,33,51 or TCD 25,52 or during cardiac catheterization, 53 patients with presumed paradoxical embolization appear to have larger PFOs compared with those in control groups. In the recent PFO in Cryptogenic Stroke Study (PICSS), it also has been shown that large PFOs were significantly more prevalent among cryptogenic stroke patients compared with those with known cause of stroke.…”
Section: Factors Associated With Paradoxical Embolization Atrial Anatomymentioning
confidence: 90%
See 1 more Smart Citation
“…With contrast TT echocardiography, 4 TE echocardiography, 32,33,51 or TCD 25,52 or during cardiac catheterization, 53 patients with presumed paradoxical embolization appear to have larger PFOs compared with those in control groups. In the recent PFO in Cryptogenic Stroke Study (PICSS), it also has been shown that large PFOs were significantly more prevalent among cryptogenic stroke patients compared with those with known cause of stroke.…”
Section: Factors Associated With Paradoxical Embolization Atrial Anatomymentioning
confidence: 90%
“…21,22 Several studies performed contrast TT, TE, and TCD imaging in the same patient group to compare the sensitivity of the techniques (Table 2). [23][24][25][26][27][28][29][30] The TE contrast study is the most sensitive diagnostic test available for detecting a PFO, followed by TCD and TT contrast studies (PϽ0.001 for TE versus TT and for TCD versus TT contrast studies).…”
Section: Transcranial Doppler In Pfo Detectionmentioning
confidence: 99%
“…S transcranial Doppler sonography (ce-TCDS) is a reliable tool for detection of RLS. [7][8][9][10][11] Depending on the method and UCA used for RLS detection, the sensitivity and specificity of the ce-TCDS method compared with the reference standard have been estimated to be between 90% and 100%. 6,12,13 With respect to the comfort of the patient, ce-TCDS is preferred over TEE as a screening tool.…”
mentioning
confidence: 99%
“…(1) The appropriate timing of the VM in relation to the injection of the contrast medium is under debate. The injection of the contrast agent was performed before, 4,[11][12][13][14][15][16][17][18] during, 15,17,19 or after the VM. 15,20 In those studies in which the VM was performed after injection, the time delay between injection and VM was frequently not clearly specified in relation to the start or the end of injection.…”
mentioning
confidence: 99%
“…22 Furthermore, the question of whether the use of a diagnostic time window for MES appearance increases the specificity of the test without necessarily decreasing sensitivity is not yet resolved. 14,23,24 Time windows proposed between the intravenous injection of the contrast medium and its appearance in the MCAs are 6 heartbeats, 20 10 seconds, 20,21 15 seconds, 13 20 seconds, 24 22 seconds, 15 and 25 seconds. 11,14 A recent study described the necessity of including MES at least 20 to 25 seconds after the start of injection to achieve a high sensitivity; it may also be possible that no time window is necessary.…”
mentioning
confidence: 99%